ANALISIS YURIDIS PEMBAGIAN HARTA BERSAMA DALAM PERKAWINAN PASCA PERCERAIAN (STUDI KASUS PUTUSAN PENGADILAN AGAMA BUKIT TINGGI NOMOR 618/PDT.G/2012/PA.BKT DAN YURISPRUDENSI MAHKAMAH AGUNG NOMOR 120K/SIP/1960) - DESICHA RATNA DEWI (PREMISE LAW JURNAL, 2016)
The settlement of joint property after divorce is stipulated in Article 37 on the Marriage Law which states that in case a marriage is dissolved due to a divorce, the joint property is stipulated accordingly to respected laws. Yet in practice the Religious Court Ruling stands more in the position that joint property after divorce must he divided equally between the divorced husband and wife. However, over the time, the Ruling of Religious Court at Bukit Tinggi No 618/Pdt.G/2012/PA.Bkt states that joint property is divided with one-third for the husband and two-third for the wife. The ruling of Religious Court at Bukit Tinggi No. 618/Pdt.G/2012/PA.Bkt decision not to follow the provisions of the Marriage Act and the compilation of Islamic law and jurisprudence of the Supreme Court rule No. 120K / Sip / 1960 by some religious court judge still followed . Religion Hill High Court judge is a justice of the view if it does not divide the joint property is not as large , the division of joint property upon divorce is considered a sense of justice are taken into consideration in determining the portion of the part of joint property. Keywords: Divorce, Share of Property, Joint Property.